THE Peran Perawat Kesehatan Kerja dalam Upaya Menurunkan Angka Kecelakaan Kerja di Kawasan Perindustrian Kota Surabaya - Ahmad An Naufal -; Sulistiawati; Sylvia Dwi Wahyuni (LPPM STIKES Guna Bangsa, 2022)
The low effectivity of occupational health and safety (OHS) application by occupational health nurses initiated a high number of work accidents, particularly in Indonesian industrial sectors. This non-optimization was generated due to insufficient guidelines to analyze the OHS among the workers. The utilization of industrial nursing care needs a protocol in order to control work accidents, one of which is using the Loss Causation Model approach. This study was aimed to explore the role of occupational health nurses in reducing the number of industrial working accidents using Loss Causation Model’s accident stages. This research was a phenomenology study with qualitative design involving 13 nurses in the industrial area of Surabaya, Indonesia. The data collection process was gained through in-depth interviews and field observation. Data analysis used Van Manen’s 6 methods and software NVIVO. These study results indicated that nurses prioritized work accident prevention, the risk of work accident identification, and maintaining occupational health and safety among workers according to the working accident stages of Loss Causation Model. In addition, nurses played a role in assessing and discovering the accident information chronologically from the health point of view. Furthermore, nurses could also suggest recommendations to policymakers in improving the workers’ welfare to diminish physical and material losses due to work accidents. It can be concluded that nurses have an important role in working accident controls, especially promotive and preventive actions, also influencing toward policy making related to OHS in the industry.